Tourists Expectations towards Agritourism - Uglis , Jarosław (Studia Oeconomica Posnaniensia, 2018)
Agritourism is of great interest, both among those who use this form of tourism as well as farmers planning to undertake such activities on their farms. The key to agritourism business success is to know the expectations and preferences of customers. The aim of the study was to identify consumer expectations of agritourism offers. Empirical research was conducted among the inhabitants of the city of Poznań by a diagnostic survey using a survey technique. The source material for the analysis was 398 questionnaires. Research has shown that the main motive for choosing agritourism as a place to spend free time for leisure or recreation purposes was the opportunity to rest in peace and quiet, low price and direct contact with nature. In the light of the presented research it can be stated that the agritourists are waiting for full board, the possibility of renting recreational equipment and buying food (eggs, milk, meat, etc.) from the farm. In addition, it has been shown that the most influential factors in choosing a particular offer are: price, standard of the facility and board.